Implantation profile for low energy positrons in diamond - Mahmuoud Aman Allah, Sabah; saad Abdual Baqi, Luma; Ahmad Daham, Najat; Amear Mahdyi, Saif (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper, Implantation profile I(z,E) and the penetration depths has been evaluated by employing a distribution function of Valkealahti-Nieminen for Diamond of differentthicknesses:0.2,0.4,0.6,0.8,1.2,1.4,1.6 Î¼m. The obtained results reveals that the Makhov,s profile decreased with increase the energy of the incident positron, and the implantation profile depths increased with an increase the energy of the incident positron.